Endodontic-Periodontic Relationship - A Short Review - Ravindranath Megha1 , Alagarsamy Venkatesh2 , Nagarajan Geethapriya3 ,Balasubramaniam Anuradha3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The relationship between periodontal and endodontic disease has been a matter of speculation for manyyears. The endodontium and periodontium influence each other during health, function and disease. Thisreview gives a fair knowledge about several aspects of endo-perio relationship. Their exist three mainpathways of communication between the pulp and periodontium. They are the apical foramen, the accessorycanals and the dentinal tubules. The apical foramen and the lateral canals come under vascular pathwayswhereas the dentinal tubule comes under the tubular pathway. The pulp and periodontal tissues are derivedfrom highly vascular mesenchymal tissues of the tooth germ. The apical foramen and lateral canals maintainthe vascular connection between these tissues throughout the tooth development.